Political Connections, CSR Integrity, and Tax Avoidance: Roles of Transparency and Enforcement - Aulia Cahya Anisa; Yunaita Rahmawati (Inovasi Analisis Data, 2025)
Purpose – This paper investigates how CSR integrity affects corporate tax avoidance through tax transparency commitments in different political and law enforcement contexts. Design/methodology/approach – This study evaluates behaviour-based governance mechanisms through a survey-based structural equation model, focusing on direct, indirect, and moderating effects. Findings – Findings indicate that stricter CSR integrity is associated with reduced tax avoidance and greater commitment to tax transparency. Tax transparency is a key factor mediating the relationship between CSR orientation and responsible tax behaviour. Political relationships weaken the impact of CSR ethics, while perceived tax enforcement strengthens the actual transparency of avoidance restrictions. Overall, the results indicate that CSR has a conditional effect on tax behaviour, in terms of internal governance and external institutional pressure. Originality/value – This study contributes to the CSR–tax literature by combining stakeholder and legitimacy theory with political economy and law enforcement perspectives into an integrated behavioural framework. The study explains why previous findings on CSR and tax avoidance are inconsistent by clearly defining a mediation model of tax transparency commitment, while considering competing sources of legitimacy. These findings imply that CSR only becomes a substantial tool when integrated with internal tax governance and continuously supported by credible law enforcement. Research Implications – This research supports the need to move beyond symbolic CSR indicators and focus on internal governance mechanisms and institutional boundaries that contribute to the manifestation of ethical corporate behaviour. It also offers a conceptual basis for incorporating tax governance into the broader ESG research agenda.